(untitled) (Academicia Globe: Inderscience Research, 2023)
The most severe form of these infection is bacterial keratitis that if not treat correctly, can lead to scarring and blindness, P. aeruginosa can commonly infect contact lens consumers causing corneal ulceration as it contaminates moist areas the areas of the eye that are commonly infected are the conjunctiva, lid and cornea.Method:Through (100) eye swabs, from 100(60 males and 40 females) were included in this study by taking eye swabs. Twenty cases (20%)with Pseudomonas aeruginosa positive isolates were found in patients who consult various hospitals in Baghdad city between March 5 and May 7, 2022. twenty (20) isolates of Pseudomonas aeruginosa were evaluated for their antibiotic susceptibility against eleven different antibiotics using Kirby-Bauer disc diffussion methods revealed varying degrees of sensitivity.